An Empirical Analysis of Cost Efficiency of the UK Commercial Banks between 2009 and 2014 - XUE, YAO (2015)
The United Kingdom is one of the global financial center, especially for the vital role of banking center within the worldwide. It is necessary to analyse the banking system that brings such contributions to the UK and worldwide. Most of the previous studies have analyzed limited datasets in years prior to the Global Financial Crisis and emplyoed with DEA which has several limitations. In this study, the purpose is to examine the cost effciency of UK commercial banks from 2009 to 2014 by SFA. In comparison with the previous studies of efficiencies of UK banks, the overall efficiency of those banks in the sample is really low. Under the estimation, the results show that the overall efficiency of UK commercial banks was increased from 2009 to 2013, and dropped in the year of 2014. It was increased approximate 5% in the first five years of the period; however, in the year of 2014, the efficiency of those banks dramatically decreased for approximate 7%. The results show that the overall average efficiency of those banks is 0.46, with the lowest score of 0.18 and the highest score of 0.65. In the year of 2012, the variance was the largest, which means that the differences between banks’ efficiencies were the largest in the period. Besides, it also indicates that those large banks categoried by the total asset are less cost efficient than those banks with smaller total asset.